Adverse events in different administration routes of Edaravone: A pharmacovigilance study based on the FDA adverse event reporting system - Deye Ge; Liyan Wu; Jingrong Yang; Jingxian Sun; Jinying Wang; Jingxin Wang; Huihui Song; Ran Wei; Zecheng Xu; Binbin Zhao; Rongfei Sun; Yifei Wang (PLoS ONE, 2026)
The U.S. Food and Drug Administration (FDA) approved intravenous edaravone for the treatment of amyotrophic lateral sclerosis (ALS) in 2017, followed by the approval of the oral formulation in 2022. This study aims to utilize the FDA#39;s Adverse Event Reporting System (FAERS) to investigate the spectrum and timing of adverse events (AEs) associated with edaravone administration, employing repeatability analysis, the Reporting Odds Ratio (ROR) approach, Weibull distribution, and stratification methods. The investigation focuses on data collected from the first quarter of 2017 through the fourth quarter of 2024, aiming to identify adverse event signals and their temporal patterns related to both intravenous and oral edaravone administration. In total, 3,262 records of edaravone-related adverse reactions were identified; among these, 1,534 incidents were associated with intravenous administration, while 453 incidents pertained to oral administration. The analysis revealed distinct adverse reaction profiles for the two routes of administration. Notably, the spectrum of adverse reactions resulting from oral administration predominantly involved the respiratory system, digestive system, and skin damage. In contrast, intravenous administration was more frequently linked to complications associated with invasive procedures and local tissue damage. Furthermore, the timing of adverse reactions exhibited significant variability between the two routes. Weibull distribution analysis indicated that the median onset time for adverse reactions following intravenous administration was 35 days, whereas for oral administration, it was 27 days. Both analytical approaches identified early failure signals, suggesting that the risk of adverse events diminishes over time.